Assembling metal‐polyphenol coordination interfaces for longstanding zinc metal anodes. Issue 3 (11th January 2022) - Huyan, Yu; Wang, Jian‐Gan; Tian, Shan; Ren, Lingbo; Liu, Huanyan; Wei, Bingqing
Abstract: Zn metals have gained the immense attention of researchers for their wide employment as the anode of high‐performance aqueous batteries. Nonetheless, the Zn anodes suffer from uncontrollable dendrite growth and parasitic side reactions, which substantially shorten the battery lifespan. This study proposes an interfacial assembly of a metal‐polyphenol coordination coating on Zn anodes to regulate Zn 2+ deposition behavior. Bismush‐coordinated polyphenolic ligands (i.e., tannic acid, TA) create a functional interface that could promote Zn's uniform nucleation and plating/striping kinetics. Moreover, the artificial coating acts as a physical barrier to inhibit surface corrosion. As a consequence, the TA‐Bi‐modified Zn anodes display a small voltage hysteresis of ~38 mV at 1 mA cm −2 over 2600 h and an ultra‐long lifespan for 3100 h (~4.3 months) even at a high‐current density of 10 mA cm −2 . When assembled with a vanadium‐based cathode, the full Zn‐ion batteries achieve improved electrochemical performance. Abstract : A functional metal‐polyphenol coordination interface is readily assembled on the Zn surface to enable uniform and dendrite‐free Zn deposition and excellent anti‐corrosion capability. The as‐modified Zn anode exhibit ultralong lifespan over 3100 h at a high‐current density of 10 mA cm −2 and improved rate/cycling performance in practical full cells.